HUBUNGAN PENGGUNAAN GADGET DENGAN PERKEMBANGAN PSIKOSOSIAL PADA ANAK USIA SEKOLAH DASAR DI SD KRISTEN EBEN HAEZAR MANADO: Penggunan Gadget dan Perkembangan Psikososial - Criselda Tampil, Velicia (STIKES ADVAITA MEDIKA TABANAN, 2026)
In the era of modern technology, almost every child uses gadgets. The use of gadgets has become a necessity for children at school in the learning process. However, continuous use of gadgets will also have an impact on children's development. One of them is related to the psychosocial development of children who will tend to focus more on gadgets than the environment around them. This study aims to determine the relationship between gadget use and psychosocial development in elementary school children at Eben Haezar Elementary School, Manado. The research method is a quantitative analytical correlational type. With a cross-sectional approach. The population in this study were 6th grade elementary school students and the total sample size was 79 students. Data were collected using a gadget usage questionnaire and psychosocial screening in children. The Pediatric Symptom Checklist is a standard questionnaire that has gone through various studies for PSC validation. Data analysis used the chi-square statistical test with a significance level of <α 0.05. The results of the study showed that respondents had sufficient gadget use, namely 53 (67.1%) respondents did not experience psychosocial development disorders as many as 57 (57%), there was a relationship between gadget use and psychosocial development in elementary school-aged children at Ebenhaezar Christian Elementary School, Manado (P-value 0.000 <0.05). The conclusion is that there is a relationship between gadget use and psychosocial development in elementary school-aged children at Ebenhaezar Christian Elementary School, Manado. Suggestions for the need for schedule arrangements and parental supervision in using gadgets in children so that children's psychosocial development becomes optimal.